Interrelation between persistent photoconductivity and oxygen order in GdBa2Cu3Ox thin films - Guimpel, J. (1997)
Fil: Guimpel, J. Comisión Nacional de Energía Atómica. Instituto Balseiro; Argentina; Universidad Nacional de Cuyo; Argentina